Pengaruh Bentuk Ungkapan Al-Ta’rif dan Al-Tankir terhadap Pemaknaan Ayat-ayat Al-Qur’an: - - Widodo, Panggih; Haniah, Haniah; Mujahid, Ahmad; Alhabsyi, Hadija; Dani, Ahmad (Journal Education And Islamic Studies, 2023)
This research is a qualitative descriptive research with a type of library research and uses primary and secondary sources. The results of this study indicate that the expressions of al-Ta'rif and al-Tankir used in the verses of the Koran have a very significant influence on the meaning of the verses of the Koran that contain these forms of expression. The use of these two forms of expression has a deep meaning and so that the verses of the Qur'an can be understood in accordance with the true intentions desired by Allah Swt. The verses of the Koran have a specific purpose, so that the interpretation of the verses of the Koran that use these two forms of expression can be fully understood as the meaning desired by the giver of revelation, namely Allah SWT. The purpose of this study is to reveal the hidden meaning of the use of the expressions al-Ta'rif and al-Tankir in the verses of the Qur'an that use these forms of expression. Apart from that, it is also to give Muslims an understanding of the influence of the forms of al-ta'rif and al-tankir in relation to the meaning of a verse.